2013
DOI: 10.1016/j.pt.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Small RNAs: a new frontier in mosquito biology

Abstract: The discovery of small non-coding RNAs has revolutionized our understanding of regulatory networks governing multiple functions in animals and plants. However, our knowledge of mosquito small RNAs are limited. We discuss here the state of current knowledge regarding the roles of small RNAs and their targets in mosquitoes, and describe the ongoing efforts to understand the role of the RNA interference (Randi) pathway in mosquito antiviral immunity and transposon silencing. Providing a clear picture into the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 84 publications
(122 reference statements)
0
40
0
Order By: Relevance
“…These processes are governed by complex regulatory networks, which have been extensively studied (5)(6)(7)(8)(9). Recent studies have also implicated microRNAs (miRNAs) in these regulatory networks in mosquitoes (10,11). miRNAs are endogenous small noncoding RNAs of 21-24 nt that are generated from either the 5′ (-5p) or 3′ (-3p) side of longer double-stranded hairpin precursors.…”
mentioning
confidence: 99%
“…These processes are governed by complex regulatory networks, which have been extensively studied (5)(6)(7)(8)(9). Recent studies have also implicated microRNAs (miRNAs) in these regulatory networks in mosquitoes (10,11). miRNAs are endogenous small noncoding RNAs of 21-24 nt that are generated from either the 5′ (-5p) or 3′ (-3p) side of longer double-stranded hairpin precursors.…”
mentioning
confidence: 99%
“…Hence, miRNAs play significant roles in governing multiple functions in animals and plants via integrating sophisticated miRNA-mRNA regulatory networks (10,11). In the mosquito, previous studies have shown that several miRNAs manipulate host-pathogen interactions, contributing to maintenance of endosymbiont Wolbachia infection or resistance to DENV (dengue virus) infection (12)(13)(14).…”
mentioning
confidence: 99%
“…Although miRNA function is a heavily studied topic in model organisms, such as the fruit fly Drosophila melanogaster, the exact functional role of miRNAs in mosquito biology remains largely unknown (5, 7). However, recent functional studies of specific miRNAs have linked miRNA action in mosquitoes to reproductive events (7,8). Studying miRNA function in the female mosquito is crucial for developing a full understanding of the regulatory processes of mosquito reproduction and may pave the way toward the utilization of these small molecules as novel approaches to control.…”
mentioning
confidence: 99%